EFEKTIVITAS MODEL PROBLEM BASEB LEARNING (PBL) BERBANTUAN MEDIA GEOFUN TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR - Fadilah, Nadra Nurul; Ardiani, Nur; Aulia, Ufa Uli; Amaliyah, Fitriyah (LPPM Institut Ahmad Dahlan Probolinggo, 2025)
The aim of this study is to determine whether the Problem Based Learning (PBL) model is one of the strategies that can be used to improve elementary school student’s mathematical problem-solving abilities. The PBL approach combined with GeoFun media is considered effective in enhancing student's problem-solving skills in mathematics. This study employed a quantitative method with pre-test and post-test design involving fifth-grade student’s of SDN 3 Loram Wetan. A total of 21 student’s (comprising 10 boys and 11 girls) were selected as research subjects using a saturated sampling technique. Test were administeres before and after the data collection, The N-Gain score of -09242, wich is below 0.3, indicates a low level of improvement. However, the 2-tailed significance test result of 0.000 < 0.05 shows a significant difference between the pre-test and post-test score. Therefore, despite the statistical difference in scores, the use of the PBL model assisted by GeoFun has not yet proven effective in helping fifth0grade student’s at SDN 3 Loram Wetan solve mathematical problem.